Breeding for resistance to bean golden mosaic virus in an interracial population of Phaseolus vulgaris L - Morales, Francisco José; Singh, Shree P. (Springer, 1993)
Eighty-three F2-derived F8 recombinant inbred lines (RILs) randomly selected from a population (TY 8419) of two common bean genotypes (Pinto UI 114 x ICA Pijao), the two parents, and a control cultivar (Topcrop) were screened for their reaction to bean golden mosaic virus (BGMV) under glasshouse conditions. A randomized complete block design with two replications was used. Data were recorded for disease incidence, foliar yellowing, number of pods and seeds, and yield. Significant (P<0.05) differences among the 83 RILs were recorded for all traits. Of these RILs, 11 lines did not develop any symptom, 24 lines had a mean disease incidence of 8%, 28 lines had a disease incidence of 26.6% and developed intermediate mosaic symptoms, and 20 lines were more susceptible (>50% disease incidence and severe yellowing) than either of the parents, which had 25% to 38% disease incidence and moderate symptoms. Heritability for disease incidence was 0.54±0.01, for foliar yellowing 0.36±0.13, for pods plant-1 0.69±0.01, for seeds plant-1 0.54±0.09, and for yield plant-1 0.49±0.01. Gains from selection (at 20% selection pressure) for these traits were 49.5%, 31.6%, 24%, 0%, and 20%, respectively, over the mean value of all RILs. Correlation coefficients between disease incidence and foliar yellowing and among yield and its components were positive. Disease incidence and foliar yellowing showed negative associations with yield and its components.